The Effect of English Grammar Application towards Students' Grammar Mastery in Present Perfect Tense - Hasanah, Siti Uswatun; Sudirman, Ade; Munawaroh, Tatu (Journal of English Education Studies, 2024)
The purpose of this research was to investigate the significant effect of an English grammar application on the students’ grammar mastery in a present perfect tense lesson at the twelfth grade of SMAN 1 Banjarsari. The research approach used a quantitative approach and a quasi-experimental method with an achievement test to collect the data. The achievement tests were pre- and post-tests. The population was 216 students, and the sample of this research was 70 students, which consisted of 35 students from the control class and 35 students from the experimental class. The control class used a simpler application, whereas the experimental class used an English grammar application for the treatment. The data was analyzed using the statistical program SPSS 22 version. Based on the data analysis result, it was determined that the different mean values of the post-test in the experimental and control classes were 68.51 and 68.14. The t-test result retrieved a signed score of 0.000 ≤ α = 0.05. The result showed that the null hypothesis was rejected and the alternative hypothesis was accepted. This means that there was a significant effect of using the English Grammar application on students’ grammar mastery in the present perfect tense lesson at the twelfth grade of SMAN 1 Banjarsari.